A historical overview and critical analysis of town centre delimitation methodologies - Pissourios Ioannis A. (Bulletin of Geography. Socio-Economic Series, 2014)
The article aims at exploring the literature on town centre delimitation methods over the last sixty years. Specifically, the first section explores the content of the term town centre, while the second one proposes an organisation of town centre delimitation research in three main periods. The third section comprises the main corpus of the article, as several town centre delimitation methodologies of the last sixty years are presented and discussed. For their presentation, a three tiered analysis is introduced. In the first stage the decisions of researchers regarding centrality estimators are discussed, in the second stage the study focuses on the choices of the spatial units, in which the chosen variables will be studied, and in the third stage the study discusses the methods that are used to characterise each of the studied spatial units as central versus non-central. Based on the analysis, the article concludes that town centre delimitation is an issue which transcends various scientific disciplines and that each of these disciplines comprehends the centre of a town in a unique way. Thus, future methods of town centre delimitation should take into account the choices made in each of the three stages presented above, and should also link the above choices to the objectives and the theoretical context of the study.